2017
DOI: 10.1007/s10509-017-3047-6
|View full text |Cite
|
Sign up to set email alerts
|

Classification of gamma-ray burst durations using robust model-comparison techniques

Abstract: Gamma-Ray Bursts (GRBs) have been conventionally bifurcated into two distinct categories dubbed "short" and "long", depending on whether their durations are less than or greater than two seconds respectively. However, many authors have pointed to the existence of a third class of GRBs with mean durations intermediate between the short and long GRBs. Here, we apply multiple model comparison techniques to verify these claims. For each category, we obtain the best-fit parameters by maximizing a likelihood functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…in the observer frame (Zitouni et al 2015;Zhang et al 2016), contrary to the findings of Horváth (2002). In case of Fermi Gamma-ray Burst Monitor (von Kienlin et al 2014;Gruber et al 2014;Narayana Bhat et al 2016), it was found that two Gaussian components suffice for the log T 90 distribution to be appropriately modeled (Bystřický et al 2012;Narayana Bhat et al 2016;Zhang et al 2016;Kulkarni & Desai 2017). The same conclusion was reached by Zitouni et al (2018) by employing pseudo-redshifts.…”
Section: Introductionmentioning
confidence: 91%
“…in the observer frame (Zitouni et al 2015;Zhang et al 2016), contrary to the findings of Horváth (2002). In case of Fermi Gamma-ray Burst Monitor (von Kienlin et al 2014;Gruber et al 2014;Narayana Bhat et al 2016), it was found that two Gaussian components suffice for the log T 90 distribution to be appropriately modeled (Bystřický et al 2012;Narayana Bhat et al 2016;Zhang et al 2016;Kulkarni & Desai 2017). The same conclusion was reached by Zitouni et al (2018) by employing pseudo-redshifts.…”
Section: Introductionmentioning
confidence: 91%
“…A third, intermediate class (Horváth 1998), remains putative. Its existence was claimed based on univariate and bivariate analyses of GRB observables modeled with Gaussian distributions (Mukherjee et al 1998;Horváth 2002;Horváth et al 2008;Zhang & Choi 2008;Huja et al 2009;Řípa et al 2009;Horváth et al 2010;Veres et al 2010;Zitouni et al 2015;Zhang et al 2016;Horváth et al 2018), but also has been put into doubt several times (Bystricky et al 2012;Řípa et al 2012;Tarnopolski 2015;Zitouni et al 2015;Narayana Bhat et al 2016;Tarnopolski 2016a,b;Ohmori et al 2016;Yang et al 2016;Kulkarni & Desai 2017;Zitouni et al 2018). Gaussian models, however, may not be the appropriate approach 1 (Koen & Bere 2012;Tarnopolski 2015;Koen & Bere 2017), as it has been already shown that the univariate distributions of T 90 (Tarnopolski 2016c,a;Kwong & Nadarajah 2018) and bivariate T 90 − H 32 ones (Tarnopolski 2019) are better described by mixtures of two skewed components rather than three Gaussian ones.…”
Section: Introductionmentioning
confidence: 99%
“…Horváth (1998) proposed the presence of a third class of GRBs by making two and three Gaussian components fits to the log 10 T90 variable of 797 GRBs in the BATSE 3B catalog. Several authors (Horváth 2002;Horváth et al 2008;Horváth 2009;Tarnopolski 2015;Horváth & Tóth 2016;Zitouni et al 2015;Huja, D. et al 2009;Horváth & Tóth 2016) have since then supported the presence of a third Gaussian component but c 2017 The Authors arXiv:1712.08123v5 [astro-ph.HE] 8 Sep 2018 Zhang et al (2016) and Kulkarni & Desai (2017) have concluded that the duration variables show a three-Gaussiancomponents model only for the Swift/ BAT dataset but a two-Gaussian-components model for the BATSE and Fermi data sets. Recently Acuner & Ryde (2018) found five types of GRBs in the Fermi catalogue.…”
Section: Introductionmentioning
confidence: 99%